2018
DOI: 10.1371/journal.pone.0207441
|View full text |Cite|
|
Sign up to set email alerts
|

Iron-enriched diet contributes to early onset of osteoporotic phenotype in a mouse model of hereditary hemochromatosis

Abstract: Osteoporosis is associated with chronic iron overload secondary to hereditary hemochromatosis (HH), but the causative mechanisms are incompletely understood. The main objective of this study was to investigate the role of dietary iron on osteoporosis, using as biological model the Hfe-KO mice, which have a systemic iron overload. We showed that these mice show an increased susceptibility for developing a bone loss phenotype compared to WT mice, which can be exacerbated by an iron rich diet. The dietary iron ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…In animal studies with different iron overload mouse models, micro-CT analysis revealed trabecular [36] as well as cortical bone loss with an increase of non-mineralized matrix and a decrease of carbonate-to-mineral ratio in FTIRI analysis indicating osteomalacia and increased bone turnover [17]. Our HHC patients also showed a reduced mineralization of the cortical bone, i.e., low Ct and BMD values.…”
Section: Pathophysiological Explanatory Approachesmentioning
confidence: 58%
“…In animal studies with different iron overload mouse models, micro-CT analysis revealed trabecular [36] as well as cortical bone loss with an increase of non-mineralized matrix and a decrease of carbonate-to-mineral ratio in FTIRI analysis indicating osteomalacia and increased bone turnover [17]. Our HHC patients also showed a reduced mineralization of the cortical bone, i.e., low Ct and BMD values.…”
Section: Pathophysiological Explanatory Approachesmentioning
confidence: 58%
“…The recovery in both arginine biosynthesis and BMD in the E2 group showed a sign of iron process revival, where a potential chance arose for the reconstruction of bone homeostasis. Under iron balanced circumstances, osteoblasts can be kept away from threats [ 66 ] and the osteoclasts number should decrease compared to the iron resorption unbalanced group [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the transport, iron remains in the blood for a very short time. However, in more extreme cases, the iron accumulates in vital organs, which contributes to the development of several diseases including hepatic cirrhosis, hepatocarcinoma, cardiac cirrhosis, diabetes mellitus, osteoarthritis, osteoporosis, and non-genetic secondary hemochromatosis also known as ‘iron-overload anemia’, as blood iron levels can be initially low with accumulated tissue levels being too high (15). This is a major reason why blood tests can be inaccurate in determining IDA.…”
Section: Discussionmentioning
confidence: 99%
“…histidine), to prevent a remarkable lowering of blood pH. It is well known that a heme group is attached to four histidines, while the iron atom in heme binds to the four nitrogens in the center of the protoporphyrin ring (14, 15). Under this condition, iron is cleaved from the heme protein to release histidine.…”
Section: Popular Scientific Summarymentioning
confidence: 99%